Effort to Improve Science Learning Outcomes with Scientific Approach in SDN 3 Randurejo - Sunarti Sunarti (Universitas Sebelas Maret, 2020)
This Classroom Action Research aims to improve the learning outcomes of Class V students in learning Healthy Food through the application of a scientific approach to Class V Students of SD Negeri 3 Randurejo, Pulokulon District, Grobogan Regency Academic Year 2020/2021. To achieve this goal, a study was conducted. The research in question is a type of classroom action research (PTK) with the dependent variable, namely, increasing the learning outcomes of grade V students in learning the Healthy Food Theme at SD Negeri 3 Randurejo for the academic year 2020/2021, while the independent variable is the use of PPT media through a scientific approach. The data collection techniques used were interviews, observation and learning outcomes tests. After the data collected will be analyzed using comparative descriptive, while for qualitative data analyzed using qualitative descriptive analysis based on the results of observation and reflection. In this classroom action research (CAR), each cycle consists of planning, implementing, observing and reflecting. With the research subjects totaling 11 students, in cycle I there were 6 students (54.54%) who completed learning, in Cycle II student learning completeness increased to students (72.72%), in cycle III student learning completeness increased to 10 students (90.90%). By looking at the learning outcomes, the application of science can improve student learning outcomes